ANALISIS HUBUNGAN ANTARA EKSTENSIFIKASI WAJIB PAJAK, SURAT SETORAN PAJAK DAN KEPATUHAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK (Students' Journal of Accounting and Banking, 2014)
To conduct a sweep or extending and improving taxpayer compliance taxpayer in delivering or reporting the amount of tax owed ​​to the Tax Payment ( SSP ) . Is one activity that is a source of tax revenue that is very important in supporting the smooth running of national development . The research objective to be achieved is to determine how the relationship of the Taxpayer Number , Tax Payment ( SSP ) , and the tax compliance of Income Tax in the Tax Office Primary Candisari Semarang. The population in this study is the individual taxpayer who carries on business and free work in 2009 - 2012 in Semarang Candisari STO , using time series data . Time series data in the form of monthly data taken directly from the data source . While the sample was selected using purposive sampling technique that samples the criteria obedient taxpayer ( in the timely delivery of tax payable by the taxpayer ) in Semarang STO Candisari during the period from 2009 to 2012 on a monthly basis . Taxpayers dutifully used as research data is Effective Taxpayers in 2009-2012 . Data used in the form of secondary data obtained from that source Taxation Information ( SPI ) , Section of Taxation Administration ( TUP ) , SIP place Integrated Services , SIP web Directorate General of Taxation . Data analysis methods used were correlation analysis and hypothesis testing using Pearson Product Moment Correlation.These results indicate that the results of the hypothesis is rejected , which means the taxpayer has a number of relationships with existing tax revenue due to the linearity relationship between the amount of the taxpayer of Revenue . While the second hypothesis is accepted , which means the Tax Payment has relationships with existing tax revenue due to the linearity relationship between the Tax Payment Receipts Tax . The results of the third hypothesis is rejected , which means the Taxpayer Compliance with Tax Filing relationship because there is the linearity of the relationship between the Taxpayer Compliance with Tax Filing.Keywords: Extensification Taxpayers, Tax Payment, Taxpayer Compliance and Tax Filing